Ecofriendly management of collar rot and web blight of cowpea - Bhadra Sree S (Department of Plant Pathology, College of Agriculture, 2007)
The study “Ecofriendly management of collar rot and web blight of cowpea was conducted at the Department of Plant Pathology, College of Agriculture, Vellayani during 2004-2007. Different plant oils, oil cakes, indigenous materials like turmeric power – baking soda and rice husk ash and biocontrol agents like Trichoderma harzianum and Pseudomonas fluorescens were used in the study to manage R. solani causing the disease.